ANALISA KEPUTUSAN INVESTASI KEUANGAN ADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UPN “VETERAN” JAWA TIMUR - Elsiva Mujityara; Eko Purwanto (Universitas Islam Kadiri, 2021)
Investment is an investment for profit in a certain period. This study aims to analyze financial literacy, financial efficacy, and financial behavior on student investment decisions. The population in this study were students of the Faculty of Economics and Business at UPN